Blood donors appointment booking and managing system using PC and mobile web browsers in current pandemic (COVID-19) - Mustafa Abdulsatar Noori; Sura Abed Sarab Hussien; Thair Abed Sarab Al-Janabi (Institute of Advanced Engineering and Science, 2021)
Blood donation is the main source of blood resources in the blood banks which is required in the hospitals for everyday operations and blood compensation for the patients. In special cases, the patients require fresh blood for compensation such as in the case of major operations and similar situations. Moreover, plasma transfusions are vital in the current pandemic of coronavirus disease (COVID-19). In this paper, we have proposed a donation system that manages the appointments between the donors and the patient in the case of fresh blood donation is required. The website is designed using the Bootstrap technology to provide suitable access using the PC or the smart phones web browser. The website contains large database including information about the donors and their blood group, available time, and other personal information to facilitate the donation process. This system is designed with unlimited abilities to be used by any hospital, blood bank, or individuals to manage the donation process with no constrains.